Overview of salt restriction in the Dietary Approaches to Stop Hypertension (DASH) and the Mediterranean diet for blood pressure reduction. - Filippou,C; Tatakis,F; Polyzos,D; Manta,E; Thomopoulos,C; Nihoyannopoulos,P; Tousoulis,D; Tsioufis,K (Rev Cardiovasc Med, 2022)
Despite considerable advances in pharmacological treatments, hypertension remains a major cause of premature morbidity and mortality worldwide since elevated blood pressure (BP) adversely influences cardiovascular and renal outcomes. Accordingly, the current hypertension guidelines recommend the adoption of dietary modifications in all subjects with suboptimal BP levels. These modifications include salt intake reduction and a healthy diet, such as the Dietary Approaches to Stop Hypertension (DASH) diet or the Mediterranean diet (MedDiet), independently of the underlying antihypertensive drug treatment. However, dietary modifications for BP reduction in adults with prehypertension or hypertension are usually examined as stand-alone interventions and, to a lesser extent, in combination with other dietary changes. The purpose of the present review was to summarize the evidence regarding the BP effect of salt restriction in the context of the DASH diet and the MedDiet. We also summarize the literature regarding the effects of these dietary modifications when they are applied as the only intervention for BP reduction in adults with and without hypertension and the potent physiological mechanisms underlying their beneficial effects on BP levels. Available data of randomized controlled trials (RCTs) provided evidence about the significant BP-lowering effect of each one of these dietary strategies, especially among subjects with hypertension since they modulate various physiological mechanisms controlling BP. Salt reduction by 2.3 g per day in the DASH diet produces less than half of the effect on systolic blood pressure (SBP)/diastolic blood pressure (DBP) (-3.0/-1.6 mmHg) as it does without the DASH diet (-6.7/-3.5 mmHg). Although their combined effect is not fully additive, low sodium intake and the DASH diet produce higher SBP/DBP reduction (-8.9/-4.5 mmHg) than each of these dietary regimens alone. It is yet unsettled whether this finding is also true for salt reductio